Analysis of the potential implementation of Material Flow Cost Accounting (MFCA) in muslim fashion SMEs Y - Pranata, M. Wahyudi; Adhariani, Desi (International Journal of Financial, Accounting, and Management, 2023)
Purpose: Conducting analysis on the current inventory control and proposing suggestions and improvements related to inventory control in SMEs Y using the Material Flow Cost Accounting (MFCA) approach. Research methodology: This research adopts a case study approach with research methods including observation, document analysis and interviews. Results: Based on the summation of raw material costs, energy costs, and system costs, the total allocation of product costs and allocation of material loss costs can be calculated. In the cost flow matrix, it is concluded that the company experiences a material loss of 7.5%. In fact, every production stage generates waste, and although the percentage of material loss may not always be significant, by reducing that percentage, the company can enhance the cost efficiency of its production. Limitations: The focus on manufactured firms especially SMEs Y limits the generalizability of the study findings to other sectors of the economy and scalability. Contributions: The results of this study can be used as a consideration in formulating policies related to the management of fashion raw material inventory in Indonesia, particularly for other SMEs in managing their inventory and if they intend to implement Material Cost Flow Accounting in their production processes.